Correction of technological characteristics of proteinfat mixture by expanding the component composition - Bochkarev, Sergiy; Varankina, Oleksandra; Bielykh, Iryna; Samoilenko, Serhii; Zviahintseva, Oksana (РC Tесhnology сеntеr, 2018)
The object of research is the technological characteristics of the protein-fat mixture of increased nutritional value, depending on the addition of vegetable oil as a component. The protein-fat mixture is a mixture of dried, crushed flax seeds – 60.00±3.00 %, sesame seeds – 25.00±1.25 % and ground sunflower seeds – 15.00±0.75 % by weight of the seed mixture. One of the most problematic places in the production technology of this product is the fine grinding of raw materials, as well as the removal of the mixture from the chopper chamber due to the high viscosity of the mass. In the course of research, it is reasonable to expand the component composition of the protein-fat mixture of increased nutritional value by adding vegetable oil based on modeling and rationalizing the technological characteristics of the product. The following technological indicators of the product are identified in this research, as the effective viscosity and the separation degree of the mixture, depending on the mass fraction of added vegetable oil. Rational amount of vegetable oil in the formulation of protein-fat mixture of high nutritional value is proved. Compared with the production of protein-fat mixture without the introduction of this component, the proposed technological solution provides the ability to overcome difficulties in fine grinding of seeds, as well as the removal of the resulting paste from the chopper chamber. It is proved the necessary to use 15 % vegetable oil to obtain a protein-fat mixture with an effective viscosity and resistance to separation in accordance with the requirements of production. According to the content of flax seeds in the protein-fat mixture is 51.00±2.50 %, sesame seeds – 21.25±1.00 %, sunflower seeds – 12.75±0.60 %. The effective viscosity of the resulting protein-fat mixture is 16.0±1.5 Pa·s, and the degree of product separation is 0.20±0.01 %. Vegetable oil as a component of the protein-fat mixture improves its technological characteristics, which, in turn, simplifies the process of dosing and packaging the resulting product.
Keywords: oilseeds; vegetable oil; effective viscosity; degree of mixture separation